The Dorsal Lunate Dislocation: A Systematic Review and Case Series - Vinograd, Ofir; Essa, Ahmad; Kachko, Arik; Persitz, Jonathan; Avisar, Erez (Journal of Wrist Surgery, 2025)
Dorsal lunate dislocation (DLD) is an exceptionally rare injury, typically resulting from high-energy trauma. Due to the scarcity of reported cases, its exact mechanism of injury is not well understood. This study aimed to present three cases of DLD treated at our institution and to perform a systematic review of the literature to evaluate the mechanisms of injury and treatment approaches for pure DLD.A retrospective review was conducted of three patients with pure DLD treated at a single tertiary care center. Data were collected through medical record analysis and radiographic review. Additionally, a systematic literature review was performed to identify reported cases of DLD. Patient demographics, mechanisms of injury, treatment modalities, and clinical outcomes were analyzed.We identified three cases of DLD, while the systematic review uncovered 17 additional cases. Overall, men represented 95% of cases, with high-energy trauma accounting for 85% of injuries. Forced wrist flexion was the most commonly reported mechanism, occurring in 55% of cases. Radiographic analysis showed concomitant wrist fractures in 55% of cases. Treatment strategies included fixation in 65% of patients, ligament repair in 45%, and lunate resection or proximal row carpectomy in 15%. The median follow-up duration was 12 months, with half of the patients achieving favorable outcomes. Notably, two of the three low-energy injury cases were associated with preexisting arthritis.Pure DLD is an extremely rare clinical entity, possibly resulting from axial loading on a flexed wrist or forced hyperflexion. Characteristic radiographic findings include disruption of Gilula's lines and dorsal displacement of the lunate on lateral radiographs. Optimal management involves initial closed reduction followed by surgical fixation and ligamentous repair when indicated to enhance outcomes and restore wrist function.
Keywords: dorsal lunate dislocation; wrist trauma; ligamentous injury; carpal instability; wrist surgery